2020
DOI: 10.1038/s41598-020-73129-6
|View full text |Cite
|
Sign up to set email alerts
|

Aenigmachannidae, a new family of snakehead fishes (Teleostei: Channoidei) from subterranean waters of South India

Abstract: Pronounced organism-wide morphological stasis in evolution has resulted in taxa with unusually high numbers of primitive characters. These ‘living fossils’ hold a prominent role for our understanding of the diversification of the group in question. Here we provide the first detailed osteological analysis of Aenigmachanna gollum based on high-resolution nano-CT scans and one cleared and stained specimen of this recently described snakehead fish from subterranean waters of Kerala in South India. In addition to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…We suspect that morphological stasis in Horaglanis may be the result of a combination of several of these factors. The small pore size of the lateritic rocks in the aquifers restricts access to this habitat for other subterranean predators such as Aenigmachanna (Britz et al 2020), resulting in a predator-free environment for Horaglanis, thus severely limiting interspecific competition. The low number of just 25 to 30 comparatively large eggs in Horaglanis (Mercy 1981) may be a response to living in a nutrient poor habitat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that morphological stasis in Horaglanis may be the result of a combination of several of these factors. The small pore size of the lateritic rocks in the aquifers restricts access to this habitat for other subterranean predators such as Aenigmachanna (Britz et al 2020), resulting in a predator-free environment for Horaglanis, thus severely limiting interspecific competition. The low number of just 25 to 30 comparatively large eggs in Horaglanis (Mercy 1981) may be a response to living in a nutrient poor habitat.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for bony fishes, with 289 valid species currently known from subterranean aquatic habitats on every continent except Antarctica (Proudlove 2022). These include some spectacular radiations of cave-adapted species , as well as lineages of 'living fossils' (Britz et al 2020). These unusual fish species have been aptly called the 'wrecks of ancient life' (Darwin 1809(Darwin -1822 and 'ghosts in the water' (Niemiller et al 2019); many of them enjoy unusual scientific names (e.g., Satan eurystomus Hubbs & Bailey, Aenigmachanna gollum Britz, Anoop, Dahanukar & Raghavan), or have emerged as laboratory models (e.g., Astyanax mexicanus (de Filippi)) for understanding evolution, development, behaviour, and human health (Krishnan and Rohner 2017;McGaugh et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that significant parts of the WG will be urbanized by 2030 due to population expansion and development ( Seto et al, 2012 ). The recent discoveries of new evolutionarily distinct lineages from the WG highlight the biogeographic and evolutionary significance of this region as well as the importance of sampling strategies to detect endemic lineages while conducting broad-level phylogenetic studies ( Britz et al, 2020 ; Chaitanya et al, 2019 ; Dinesh et al, 2020 ; Mallik et al, 2019 ; Pal et al, 2018 ; Robin et al, 2017 ; Vijayakumar et al, 2019 ). The recognition of 10 new morphologically distinct and geographically isolated species of Cnemaspis from the SWG also highlights our lack of knowledge regarding the immense diversity of this region and its potential to harbor more unknown species.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these species are evolutionary relics of an ancient fauna, often with long-term isolation in these high-stress environments (Gibert and Deharveng 2002). Such evolutionarily relictual lineages include among others, the Aenigmachannidae -a "living fossil" with a putative Jurassic origin (Britz et al 2020), the enigmatic Kryptoglanidae (Britz et al 2014), the cistern catfish Phreatobius (Muriel-Cunha and de Pinna 2005), and the blind aquifer-dwelling Horaglanis (Raghavan et al 2023). However, the large majority of cavefishes represent "young" lineages that have much more recently invaded subterranean habitats -examples include the European cave loach, Barbatula sp., and the Mexican blind swamp eel, Ophisternon infernale (Behrmann-Godel et al 2017;Mar-Silva et al 2022).…”
Section: Introductionmentioning
confidence: 99%